Réponses

2014-10-26T15:21:05+01:00
(3x-4)² - (3x-4)(5-2x).

1. C=(3x-4)² - (3x-4)(5-2x)
      =(3x)² - 2×4×3x + 4² - 3x ×5 + 3x × (-2x) - 4 × 5 - 4 × (-2x)
      = 9x² - 24x + 16 - 15x + ( -6x² ) - 20 - (-8x)
      = 9x² - 24x + 16 - 15x - 6x² - 20 + 8x
      = 3x² - 31x - 4.

2. C=(3x-4)² - (3x-4)(5-2x)
      =(3x-4)(3x-4)-(3x-4)(5-2x)
      =(3x-4) ((3x-4)-(5-2x))
      =(3x-4) (3x-4-5+2x )
      =(3x-4) (5x-9)

3. (3×0-4) (5×0-9) = (-4)(-9) = -4×(-9) = 36
tu fais pareille pour le reste je t'ai fait la 3.a .